2020
DOI: 10.1002/osp4.403
|View full text |Cite
|
Sign up to set email alerts
|

Modeling interactions between brain function, diet adherence behaviors, and weight loss success

Abstract: Introduction: Obesity is linked to altered activation in reward and control brain circuitry; however, the associated brain activity related to successful or unsuccessful weight loss (WL) is unclear.Methods: Adults with obesity (N = 75) completed a baseline functional magnetic resonance imaging (fMRI) scan before entering a WL intervention (ie,3-month diet and physical activity [PA] program). We conducted an exploratory analysis to identify the contributions of baseline brain activation, adherence behavior patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…In contrast, patients who underwent laparoscopic sleeve gastrectomy surgery exhibited decreases in body weight and in reported food cravings 1 and 6 months post-surgery that were associated with the increased connectivity to the prefrontal regions in the brain in response to food cues [ 76 ]. Another recent study showed that success in a 3-month weight loss program was predicted by activity in the prefrontal cortex in response to food cues [ 77 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, patients who underwent laparoscopic sleeve gastrectomy surgery exhibited decreases in body weight and in reported food cravings 1 and 6 months post-surgery that were associated with the increased connectivity to the prefrontal regions in the brain in response to food cues [ 76 ]. Another recent study showed that success in a 3-month weight loss program was predicted by activity in the prefrontal cortex in response to food cues [ 77 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the importance of dopaminergic reward areas was underlined by CR studies showing that cue-evoked activity in these areas is negatively related to treatment outcome [173][174][175][176][177]. The relevance of goal-directed control regions comprising frontal and parietal areas as well as insula was demonstrated in DD tasks directly designed to study goal-directed control [18,97,104,106] and in CR tasks by showing that cue-related activity of these areas has a positive effect on treatment outcome [86,169,[178][179][180]. Task-derived FC and RS FC studies showed that higher FC between fronto-parietal and insular goaldirected control areas on one hand and incentive salience areas on the other is accompanied by better treatment outcomes [18,97,99,100,126].…”
Section: Discussionmentioning
confidence: 99%
“…This would take multiple neuroimaging, hormonal, and outcome markers (see e.g., [18,163,179]) into consideration. In this regard, the study of Szabo-Reed and colleagues might be pioneering as complex associations between brain activity, caloric restrictions, program attendance, physical activity and weight loss were modeled within a single structural equation model in this work [169]. This approach does not only promise to reveal a more fine-grained picture of contributing factors but also In conclusion, the reviewed studies provide consistent support for the importance of incentive salience and goaldirected control as central nervous mechanisms mediating treatment outcome in obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study sought to expand neuroanatomy and function research [ 23 , 24 ] to predict change in response to food and non-food stimuli and investigate event-related potentials (ERPs) relevant to response-inhibition in patients with PWS using a Go/NoGo task with food vs. non-food cues assessed via ERPs. Based on prior work, tDCS was hypothesized to modulate expected patterns of ERPs to demonstrate enhanced response-inhibition associated with processing of food-related stimuli.…”
Section: Introductionmentioning
confidence: 99%